Encyclopedia of psychopharmacology - Stolerman, Ian P.; Price, Lawrence H. (Springer Berlin Heidelberg Imprint: Springer, 2015)
Psychopharmacology is the study of the effects of psychoactive drugs on the functioning of the central nervous system at all levels of analysis, thus embracing cognition, behavior, psychological states, neurophysiology, neurochemistry, gene expression, and molecular biology. It includes, as an integral part of its domain, the interaction of environmental and genetic factors with psychoactive drug action, the medicinal and social uses of drugs, and the misuse and abuse of psychoactive substances. The aim of this comprehensive encyclopedia is to provide detailed information on psychopharmacology and its sub-disciplines, such as clinical psychopharmacology, molecular neuropsychopharmacology, behavioral pharmacology in laboratory animals, preclinical psychopharmacology, and human experimental psychopharmacology. The wide-ranging entries in the Encyclopedia of Psychopharmacology are written by leading experts drawn from a broad diversity of backgrounds and areas of specialization. The entries, comprehensive but succinct, provide basic and clinical scientists in academia, as well as industry, with the most important and relevant information on recent developments in psychopharmacology and its closely allied disciplines. The essential information about the field contained in these entries is readily accessible to clinicians, scholars, students, teachers, and interested laypeople.